2006
DOI: 10.4049/jimmunol.176.11.6709
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-θ-Mediated Signals Enhance CD4+ T Cell Survival by Up-Regulating Bcl-xL

Abstract: Productive engagement of TCR results in delivering signals required for T cell proliferation as well as T cell survival. Blocking TCR-mediated survival signals, T cells undergo apoptosis instead of proliferation upon TCR stimulation. During the activation process, T cells produce IL-2, which acts as an extrinsic survival factor. In addition, TCR stimulation results in up-regulation of Bcl-xL to enhance T cell survival intrinsically. We show in this study that protein kinase C (PKC)-θ is required for enhancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 44 publications
4
82
1
Order By: Relevance
“…This defect reflects the deficient activation of the transcription factors NF-B, AP-1, and NF-AT (3)(4)(5), consistent with observations that PKC, but not other T cell-expressed PKCs, activate the corresponding reporter genes in T cells (6). In addition, PKC is essential for T cell survival, modulating the expression or activity of Bcl-2 family members (7)(8)(9)(10).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This defect reflects the deficient activation of the transcription factors NF-B, AP-1, and NF-AT (3)(4)(5), consistent with observations that PKC, but not other T cell-expressed PKCs, activate the corresponding reporter genes in T cells (6). In addition, PKC is essential for T cell survival, modulating the expression or activity of Bcl-2 family members (7)(8)(9)(10).…”
supporting
confidence: 56%
“…For Transwell experiments, isolated NK cells and NK-depleted splenocytes were placed, respectively, in the upper and lower chambers of a 24-well Transwell plate in the presence or absence of poly(I:C) during 16 h. Then, NK cells were recovered for Western blot analysis. Finally, for IL-12 and IL-15 time course experiments, 10 5 purified NK cells were cultured in the presence of 100 ng/ml mouse rIL-12 (Invitrogen) or IL-15 (Calbiochem) during the times indicated, and both PKC expression and phosphorylation were analyzed as indicated above.…”
Section: Analysis Of Pkc Activation and Expression In Nk Cellsmentioning
confidence: 99%
“…PKC has been shown to modulate the activities of many transcription factors including nuclear factor of activated T cell c2, NF-B, and activator protein-1 (47), and several lines of evidence indicate PKC to also be involved in transcriptional repression by modulating nuclear receptor-corepressor and/or -coactivator interaction in T lymphoid cells (48) (49). Because significant increases in caspase-3 activity were detected in C2C12 myotubes exposed to saturated FFAs but not unsaturated FFAs, the suppression of sortilin mRNA expression observed herein might be a consequence of apoptotic responses to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have supported a role for PKCy and c-Rel in survival via induction of Bcl-X L [30][31][32]. Thus, c-Rel may also play a role in regulating peripheral tolerance by controlling survival versus elimination of potentially self-reactive cells.…”
Section: The Induction Of Anergy Is Not a Consequence Of Impaired Surmentioning
confidence: 99%
“…It has recently been shown that signaling through PKCy leads to the induction of Bcl-X L [30,31] and that this upregulation of Bcl-X L is dependent on c-Rel but is independent of p50 [32]. Furthermore, overexpression of Bcl-X L prevents the induction of tolerance in several transplantation models [33,34].…”
Section: Bcl-x L Does Not Restore T-cell Functionmentioning
confidence: 99%